2008
DOI: 10.1097/tp.0b013e3181821cad
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Down-Regulates the Primate Cellular Response to Porcine Aortic Endothelial Cells In Vitro

Abstract: Using MLR, the effect of atorvastatin on proliferation of human and baboon PBMC and human CD4+T cells in response to wild-type (WT) and α1,3-galactosyltransferase gene-knockout (GTKO) porcine aortic endothelial cells (pAEC) was investigated. SLA class-II expression on pAEC before and after pIFN-γ stimulation, and the effect of atorvastatin on this expression was assessed. Added to the MLR, atorvastatin reduced (i) the human PBMC response to unstimulated (p<0.05) and (ii) the human and baboon PBMC responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Anti-inflammatory agents prevent TF expression and thrombosis (63). For example, we have shown that statins inhibit upregulation of TF expression on pig endothelial cells in response to primate xenoreactive antibodies (64) and regulate human and baboon T cell proliferation against pig endothelial cells (65). …”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory agents prevent TF expression and thrombosis (63). For example, we have shown that statins inhibit upregulation of TF expression on pig endothelial cells in response to primate xenoreactive antibodies (64) and regulate human and baboon T cell proliferation against pig endothelial cells (65). …”
Section: Discussionmentioning
confidence: 99%
“…12 Anticipating similar responses with endothelialized modules, we used tacrolimus, an immune-suppressant, and atorvastatin to enhance allograft survival. Atorvastatin may directly decrease the immune response to EC as demonstrated by decreased proliferation of T cells exposed to xenogeneic EC in vitro, 13 improved EC survival, 14 increased NO production, 15,16 and increased number of circulating endothelial progenitor cells. 17 With tacrolimus and atorvastatin treatment, inflammatory cell numbers (CD68 þ ) were significantly reduced at day 21 (Fig.…”
Section: Tissue Vascularization and Impact Of Inflammation And Immunementioning
confidence: 99%
“…For example, pigs expressing the immunoregulatory molecule CTLA4-Ig have been produced [24] [25], and anti-inflammatory agents have been shown to reduce the human T cell response to pig cells in vitro [16]. Our previous studies indicated that a large number of MSC can be effectively harvested from GTKO/CD46 pig fat tissue [26].…”
Section: Discussionmentioning
confidence: 99%
“…Adherent cells were harvested using trypsin-EDTA (Invitrogen, Grand Island, NY) when MSC reached 90–95% confluence. pAECs were obtained from freshly-harvested GTKO pigs aortas, and cultured as previously described [16]. Both pMSC and pAEC were used from passages 2–6.…”
Section: Methodsmentioning
confidence: 99%